Design of steel fiber reinforced concrete beams for shear using inverse analysis for determination of residual tensile strength. (25th September 2017) - Foster, Stephen J.; Agarwal, Ankit; Amin, Ali
Abstract : The behavior of steel fiber reinforced concrete (SFRC) has been extensively investigated in the last four decades. For the most part, however, existing design models for shear are based on empirical equations where fiber–concrete is considered as a unique material and fibers and concrete components to shear are considered collectively, or where the concrete and fiber components to shear are considered separately and each are derived independently. As demonstrated in this paper, the problem with this latter approach is that the influence of the concrete and the fiber components are each affected by the other—that is, they are coupled. In this paper, a rational model is outlined for determining one‐way shear strength of SFRC beams and slabs. The model is developed from the modified compression field approach with due consideration given to the inter‐relationship between the concrete–steel–fiber components to the shear resistance. Introduced into the model is an inverse analysis method for determining the post‐cracking residual tensile strength of SFRC from prism bending tests, a core materials property needed for design. In determining this strength, due attention is provided to the influences of notches, specimen boundaries and bias in fiber orientation that occurs as part of the casting process. The results of the design model predictions are compared with a dataset of test specimens collected from the literature, with very good correlation observed.